Rapid identification method for distinguishing true and false high-stress fireproof glass by using flame impact and stress release

Through the methods of flame impact and stress release, high-stress fire-proof glass is quickly identified, which solves the problems of long detection cycle and high cost in the existing technology, improves fire safety, and achieves rapid and accurate distinction on site.

CN119224203AInactive Publication Date: 2024-12-31招商局检测认证(重庆)有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410729632.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-06
Publication Date
2024-12-31
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, fireproof glass inspection needs to be carried out at a national testing center, with a long inspection cycle, high cost and unsuccessful completion at the project site, and there is a serious fire safety hazard that tempered glass is pretended to be fireproof glass.

Method used

Using flame impact and stress release methods, vertical flame impact on glass samples with a thickness of 1200mm×700mm for 10 minutes. If it is not exploded, spray room temperature water to observe the burst time and number of broken particles to distinguish between true and false high-stress fire-proof glass .

Benefits of technology

It realizes rapid identification of high-stress fire-resistant glass on site, avoids long-term inspection and high costs, improves fire safety, and accurately distinguishes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a rapid identification method for distinguishing true and false high-stress fireproof glass by flame impact and stress release, which comprises the following steps: S1, test preparation: taking a to-be-tested glass sample with the thickness of 6mm and the size of 1200mm * 700mm, and vertically placing the to-be-tested glass sample on a test rack by taking the long side as the bottom; s2, sample testing: performing vertical flame impact on the to-be-tested glass sample for 10 minutes, then stopping flame impact, and spraying a certain amount of room-temperature water on the impact part; and S3, sample judgment: when the to-be-detected glass sample does not explode within 10 minutes after being impacted by flames, the to-be-detected glass sample is wholly exploded within 5 minutes after being sprayed with room-temperature water, broken particles generated by explosion are small, and the number of the broken particles is not less than 400, the to-be-detected glass sample is qualified fireproof glass. As the fireproof glass has surface stress which is higher than that of the tempered glass, thermal expansion impact force brought by flames can be resisted, and after fire attacks and quenching spraying, the high-stress fireproof glass bursts before the tempered glass, so that whether the high-stress fireproof glass is the high-stress fireproof glass or not can be quickly judged through flame impact and stress release.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of testing fireproof glass, and specifically relates to a rapid identification method for distinguishing true and false high-stress fireproof glass by flame impact and stress release, which is suitable for rapid qualitative determination of product quality of high-stress fireproof glass. Background Art

[0002] Fireproof glass refers to glass that can maintain a closed structure and prevent the spread of flames and smoke in the installed frame within a limited time after a fire occurs, or has functions such as heat insulation and reducing thermal radiation. Fireproof glass can be classified as follows according to GB 15763.1-2009 "Safety Glass for Buildings Part 1: Fireproof Glass":

[0003] Structural classification: composite fireproof glass (FFB), single-piece fireproof glass (DFB). Special glass composed of two or more layers of glass or one layer of glass and organic materials and meeting the corresponding fire resistance requirements is composite fireproof glass, and special glass composed of single-layer glass and meeting the corresponding fire resistance requirements is single-piece fireproof glass.

[0004] Classification by fire resistance performance: Insulating fireproof glass (Class A), non-insulating fireproof glass (Class C). Insulating fireproof glass is the glass that meets both fire resistance integrity and fire insulation requirements, while monolithic fireproof glass is the glass that only meets fire resistance integrity requirements.

[0005] At present, the single-piece fireproof glass on the market mainly includes high-stress soda-lime-silica glass and borosilicate fireproof glass. Among them, the principle of high-stress soda-lime-silica glass is similar to that of ordinary tempered glass, but the stress on the surface of the glass is higher, generally above 160MPa. Borosilicate fireproof glass mainly achieves fireproof function due to its low expansion coefficient and higher softening point.

[0006] At present, some companies use tempered glass to impersonate fireproof glass. Since tempered glass does not have fireproof function, it cannot be installed in fireproof areas, so there are serious fire safety hazards. In the existing technology, when testing fireproof glass, it is necessary to conduct fire resistance tests according to GB / T12513-2006. However, this test can only be completed in several professional testing institutions such as national fire testing centers. It not only requires a large-scale fire-resistant component test furnace, but also has problems such as long testing cycle and high testing cost, which ordinary people cannot afford. What's more important is that the fireproof glass test specified in the standard cannot be completed at the project site. Summary of the invention

[0007] The present invention intends to provide a rapid identification method for distinguishing true and false high-stress fireproof glass by flame impact and stress release, which can quickly determine whether the glass to be tested is high-stress fireproof glass.

[0008] To this end, the technical solution adopted by the present invention is: a rapid identification method for distinguishing true and false high-stress fire-resistant glass by flame impact and stress release, comprising the following steps:

[0009] S1 Test preparation: Take a 6mm thick, 1200mm×700mm glass sample to be tested and place it vertically on the test stand with the long side as the bottom;

[0010] S2 sample test: vertical flame impact is applied to the geometric center of any corner area of ​​the glass sample to be tested for 10 minutes and observed whether it explodes, and the flame temperature reaches above 1200℃. If the glass sample to be tested does not explode within 10 minutes of impact, the flame impact is stopped, and then a certain amount of room temperature water is sprayed on the impacted part to observe the time required for the explosion and the number of broken particles produced;

[0011] S3 sample judgment: When the glass sample to be tested does not explode within 10 minutes of flame impact, and explodes as a whole within 5 minutes after being sprayed with room temperature water, and the fragments produced by the explosion are small, opaque milky white, and the number of fragments is not less than 400, it is high stress fireproof glass.

[0012] As a preferred embodiment of the above scheme, in S2, the size of the corner area is 40 mm×40 mm, and the volume of the sprayed room temperature water is between 400 mL and 500 mL.

[0013] More preferably, the method for calculating the number of broken particles in S3 is to first place a counting frame of a certain size at the part where the fragments are most densely packed, and then calculate the number of broken particles on two adjacent sides of the counting frame, and the product of the numbers is the total number of broken particles.

[0014] The beneficial effects of the present invention are as follows: since the high-stress fireproof glass has a surface stress higher than that of the tempered glass, the high-stress fireproof glass can resist the thermal expansion impact force brought by the flame, and after the fire attack and the rapid cooling spray, that is, after the new impact stress is generated on the glass sample to be tested, the high-stress fireproof glass explodes before the tempered glass, so that it can be quickly distinguished and judged whether it is high-stress fireproof glass through the flame impact and stress release, without the need for long-term experiments in the laboratory. DETAILED DESCRIPTION

[0015] The present invention will be further described below by way of examples:

[0016] A rapid identification method for distinguishing true and false high-stress fire-resistant glass by flame impact and stress release mainly includes the following steps:

[0017] Step 1: Test preparation: Take a 6mm thick, 1200mm×700mm glass sample to be tested and place it vertically on the test stand with the long side as the bottom. The sample stand adopts the existing technology, including a test bench and a clamping assembly arranged on the left and right of the test bench for clamping the lower end of the glass sample to be tested, and the clamping assembly includes two clamping blocks arranged at intervals in front and back, and the clamping blocks can be clamped manually or electrically.

[0018] Step 2: Sample testing; subject the glass sample to vertical flame impact at the geometric center of any 40mm×40mm corner area for 10 minutes and observe whether cracking occurs, and the flame temperature reaches above 1200℃. If the glass sample does not crack within 10 minutes of impact, stop the flame impact, and then spray 400mL-500mL of room temperature water on the impact site to observe the time required for cracking and the number of fragments produced.

[0019] The flame used is the inner flame of a commercially available 95% butane blowtorch with a temperature of more than 1200°C. The blowtorch is also fixed on a clamping rod with a movable part, and the clamping rod can be set as a telescopic rod. The part of the clamping rod that fixes the blowtorch can use a clamping claw, which can be a manual spring structure or an automatic structure.

[0020] Step 3: Sample determination: When the glass sample to be tested meets the following conditions, it is qualified as high-stress fire-resistant glass: the conditions are: no cracking occurs within 10 minutes of flame impact, and after spraying room temperature water, it explodes as a whole within 5 minutes, and the fragments produced by the explosion are small, opaque milky white, and the number of fragments is not less than 400.

[0021] The method for calculating the number of broken particles is to first place a 50mm×50mm counting frame at the part where the fragments are most densely packed, and then count the number of broken particles on the two adjacent sides of the counting frame. The product of the two is the total number of broken particles. When counting the number of broken particles in the counting frame, it is best to equip it with a magnifying glass, or take a photo and enlarge it for counting. Fragments that cross the edge of the counting frame or broken particles separated by cracks can be counted as 1 broken particle.

[0022] In order to verify the accuracy of this method, the following test is first carried out.

[0023] In the first step, take 6mm thick, 1200mm×700mm float glass (i.e. original glass), semi-tempered glass, tempered glass and high stress fireproof glass (soda-lime-silica high stress fireproof glass), and place them vertically on the test frame with the long side as the bottom edge.

[0024] In the second step, a commercially available 95% butane torch with an internal flame of more than 1200°C was used to vertically impact the geometric center of any 40mm×40mm corner area of ​​the four types of glass for 10 minutes. Then, for the glass that did not explode, 400mL-500mL of room temperature water was used to spray the flame impact part to quickly cool it down.

[0025] The third step is to observe the entire test process. It is found that during the impact process, the corners of float glass exploded about 2 minutes after the flame impact, while the other three types of glass did not explode within 10 minutes of impact. During the spray rapid cooling process and a period of time after cooling, the corners of semi-tempered glass exploded rapidly. The impact part of high-stress fireproof glass cracked rapidly, and then usually exploded as a whole within 5 minutes, with small fragments, opaque milky white fragments, and the number of fragments ≥ 400. The impact part of ordinary tempered glass cracked rapidly, and the overall explosion time was longer than that of high-stress fireproof glass, usually about 30 minutes, and some did not even explode, but when the edge of the impact part of the tempered glass was gently tapped with external force, the tempered glass would instantly explode as a whole, the fragments were transparent, the fragments were large, and the number of fragments was <400, about 200.

[0026] The reasons why the four types of glass produce different phenomena after fire attack and rapid cooling spray are as follows:

[0027] The reason why float glass explodes when burned: the original glass has not been tempered, the surface stress is about 5MPa, which shows low impact strength and is unable to resist the thermal expansion impact caused by the flame.

[0028] The reason why semi-tempered glass does not explode during the flame impact process but quickly explodes after water spraying: semi-tempered glass has undergone proper tempering treatment and has a certain surface stress of about 50MPa, which is much higher than float glass but lower than the surface stress of tempered glass. It can resist the thermal expansion caused by flame impact, so it will not explode when exposed to fire. However, semi-tempered glass explodes quickly after 10 minutes of flame impact and spraying. The main reason is that during the flame impact process, the glass surface is subjected to continuous high temperature impact of 1200℃, the impacted part of the glass surface is slightly melted, and the surface stress of the impacted part is released, which is rapidly cooled by water, causing the corners of the semi-tempered glass to shrink and explode.

[0029] The reason why tempered glass and high-stress fireproof glass do not explode during the flame impact process is that the surface stress of these two types of glass is large, which can resist the thermal expansion caused by the flame impact for 10 minutes. After spraying and rapid cooling, they can also temporarily resist the influence of thermal expansion and contraction, showing that they did not immediately explode as a whole after spraying and rapid cooling, or only cracked at the impact site. However, in the subsequent process, high-stress fireproof glass exploded within 5 minutes, while the explosion time of tempered glass was longer, about 30 minutes, and some tempered glass did not even explode. The time difference between high-stress fireproof glass and tempered glass in the overall explosion is very large. The main reason is that the compressive stress and tensile stress inside the two types of glass are different, and the time to reach the allowable strength of the glass is different.

[0030] The difference between the tensile and compressive stresses of tempered glass and high-stress fireproof glass is that tempered glass and high-stress fireproof glass mostly form compressive stress on the glass surface through physical tempering to improve the strength of the glass. However, while compressive stress is formed on the glass surface, tensile stress exists inside the glass. Physically tempered glass is a stress balance body with a symmetrical parabola of stress distribution. The surface layer is compressive stress and the middle layer is tensile stress. The compressive stress is the largest on both sides of the glass. Research data show that the surface compressive stress is generally 2.5 times the maximum tensile stress in the middle. It can be seen that the greater the compressive stress on the glass surface, the greater the tensile stress inside.

[0031] The allowable strength of glass is a constant, also known as tensile strength. Once the tensile stress inside the glass exceeds its allowable strength, the glass will break. Taking the 6mm ordinary tempered glass and high-stress fireproof glass commonly seen on the market as examples, the surface stress of tempered glass is measured to be 100Mpa, and the surface stress of high-stress fireproof glass is 160Mpa. It can be estimated that the tensile stress inside the tempered glass is 40Mpa, and the tensile stress inside the high-stress fireproof glass is 64Mpa. Therefore, high-stress fireproof glass shows that it is easier to reach its allowable strength than ordinary tempered glass. Therefore, when subjected to the tensile force caused by external impact, high-stress fireproof glass will burst before tempered glass.

[0032] The fire attack and rapid cooling spray on the tempered glass and high-stress fireproof glass in the above test is essentially a re-tempering process, which also brings new impact tension to the two types of glass. This new impact tension is superimposed on the original tensile stress, and the high-stress fireproof glass will burst before the tempered glass. If the tensile superposition effect brought by the above test inside the tempered glass does not exceed its allowable strength, it will show that the tempered glass will not burst. However, at this time, there are already tensile stress and new impact tension inside the tempered glass, and there is only a small interval value from the allowable strength. Only a small knocking force is needed to superimpose a little tensile stress to cause the tempered glass to burst as a whole.

[0033] In order to further verify whether the method for calculating the number of broken particles of high-stress glass is feasible, 5 pieces of 6mm thick high-stress fireproof glass and 5 pieces of 6mm thick tempered glass were randomly selected, and the high-stress fireproof glass was numbered 1-5, and the tempered glass was numbered 1#-5#. This method was used to conduct experiments, and finally the number of broken particles after the explosion was calculated by this counting method, as shown in Table 1 below.

[0034] Table 1 The number of broken particles after 5 high-stress fireproof glasses and 5 tempered glasses were shattered

[0035] Sample No. Number of broken pieces (pieces) 1 551 2 560 3 532 4 609 5 570 1# 194 2# 165 3# 187 4# 194 5# 187

[0036] Through the above test, it can be clearly seen that the number of fragments produced by the explosion of high stress fireproof glass using this method is greater than or equal to 400, while the number of fragments of tempered glass is less than 400. Therefore, the counting method of this method can be used as a distinguishing point between tempered glass and high stress fire extinguishing glass.

[0037] In order to further verify the accuracy of the qualitative judgment of this method, 12 pieces of float glass, semi-tempered glass, tempered glass and soda-lime-silicon high-stress fire-resistant glass produced by three different manufacturers on the market were found, and the thickness of each piece was 6 mm. At the same time, the glass was marked and numbered 1#-12# randomly. The personnel were replaced to test them using this method, and the results are shown in Table 2.

[0038] Table 2 Test results of different glasses

[0039]

[0040]

[0041] After the test, the person who shuffled the numbers was asked to tell the types of 12 glass with different numbers, among which 4#, 12#, 3#, and 8# were float glass, semi-tempered glass, tempered glass, and soda-lime-silicon high-stress fireproof glass from manufacturer A, 5#, 1#, 6#, and 9# were float glass, semi-tempered glass, tempered glass, and soda-lime-silicon high-stress fireproof glass from manufacturer B, and 11#, 2#, 7#, and 10# were float glass, semi-tempered glass, tempered glass, and soda-lime-silicon high-stress fireproof glass from manufacturer C. It can be seen from the above test results that float glass exploded in about 2 minutes under flame impact, and the other three types of glass did not explode in 10 minutes of flame impact. Continue to spray the flame impact part of the unbroken glass, and the results are: in terms of overall explosion time, semi-tempered glass < high-stress fireproof glass < tempered glass; particle size: high-stress fireproof glass < tempered glass; particle quantity: tempered glass < high-stress fireproof glass. The number of broken particles of high-stress fire-resistant glass is greater than 400, while the number of broken particles of tempered glass is less than 400. The specific number is around 200.

[0042] The remaining glass after taking out the test sample was sent to the National Fire Protection and Flame Retardant Product Quality Inspection and Testing Center (Chongqing) for testing, and it was found that 8#, 9#, and 10# were high-stress fireproof glass, that is, the test results of the present application method were consistent with the test results of the National Fire Protection and Flame Retardant Product Quality Inspection and Testing Center (Chongqing). Therefore, it is possible to quickly determine whether it is high-stress fireproof glass by flame impact and stress release.

Claims

1. A rapid identification method for distinguishing true and false high-stress fire-resistant glass by flame impact and stress release, characterized in that: The following steps are involved: S1 Test preparation: Take a 6mm thick, 1200mm×700mm glass sample to be tested and place it vertically on the test stand with the long side as the bottom; S2 sample test: vertical flame impact is applied to the geometric center of any corner area of ​​the glass sample to be tested for 10 minutes and observed whether it explodes, and the flame temperature reaches above 1200℃. If the glass sample to be tested does not explode within 10 minutes of impact, the flame impact is stopped, and then a certain amount of room temperature water is sprayed on the impacted part to observe the time required for the explosion and the number of broken particles produced; S3 sample judgment: When the glass sample to be tested does not explode within 10 minutes of flame impact, and explodes as a whole within 5 minutes after being sprayed with room temperature water, and the fragments produced by the explosion are small, opaque milky white, and the number of fragments is greater than or equal to 400, it is high-stress fire-resistant glass.

2. The rapid identification method for distinguishing true and false high-stress fireproof glass by flame impact and stress release according to claim 1, characterized in that: In S2, the size of the corner area is 40 mm × 40 mm, and the volume of sprayed room temperature water is between 400 mL and 500 mL.

3. The rapid identification method for distinguishing true and false high-stress fireproof glass by flame impact and stress release according to claim 1, characterized in that: The method for calculating the number of broken particles in S3 is to first place a 50 mm × 50 mm counting frame at the part where the fragments are most densely packed, and then count the number of broken particles on both sides of the counting frame, and the product of the two numbers is the total number of broken particles.

Citation Information

Patent Citations

  • Nondestructive testing method for fireproof glass

    CN112285058A

  • Fire-resistant glass materials

    GB1476869A

  • Tempered glass sheet, process and apparatus therefor

    US20040007022A1